Genome sequence of nitratireductor aquibiodomus strain RA22 - Singh, Ajit; Jangir, Pramod Kumar; Kumari, Chanchal; Sharma, Rakesh (Journal of Bacteriology, 2012)
The genus Nitratireductor represents nitrate-reducing bacteria from the family Phyllobacteriaceae. Here we report the draft genome sequence of Nitratireductor aquibiodomus strain RA22, which contains 4,592,790 bp, with a G+C content of 61.30%, and has 4,241 protein coding genes.